CARA IBU MENGATASI KESULITAN MAKAN PADA ANAK PRA SEKOLAH DI DESA PENYENGAT OLAK KABUPATEN MUARO JAMBI TAHUN 2015 - Afridawaty MJ (Universitas Batanghari Jambi, 2018)
Preschool children was the children who aged 3 to 5 years. The Groth and development of pre school children was influenced by the nutrition, activity, sleeping problem, dental health, prevention of an injury, and the parenting style.The nature of typical development influence children’s eating patterns such as a child being too picky. Difficulty eating is when a child is unwilling or refuses to eat with the type or amount of physiologicalage appropriate. The pre school age children who have difficulty eating and can further lead to complication a and impaired child development, so we need a way to overcome adversity mother eating in children.The aimed of study was to determine the description how mothers cope with eating problem in pre school children in Penyengat Olak Village Muaro Jambi. This study was a quantitative descriptive. The sampling technique was simple random sampling wit 38 Persons were being the sample. The result showed from 38 respondent, 21 respondent (55,2%) less well in dealing with eating problem in children. Difficulty eating in children ia an important issue for older people, if not treated early. It is expected the parents, especially the mother can detect the caused difficulty eatingin children so that treatment can be done quickly and accurately, and the parent were suggested applied the appropriate parenting style for the preschool children to maximize the aptitude. Key word : Difficulty eating, mothers, pre school children